Prevalence of Tuberculosis in Nasiriyah City from 2010-2015 - Kadhim Mohan Manhil (Journal of Global Pharma Technology, 2016)
Tuberculosis deployed in Nasiriyah City this study aimed to prevalence of Tuberculosis in Nasiriyah City, It is during visit to the health centers in the first and second Nasiriyah sector and updating us on the data found where the number of total infections in Nasiriyah from a year 2010 and 2015 to 2821 cases distributed among different age groups where the infection rate among children 5% and women 25% and men 70% and through study and observation of the database and the number of cases. low that number infection case in 2015 than it was in 2010 where the number of people with tuberculosis in 2010 in 628 infection case in 2015 was 260 cases and this shows a lower incidence gradually The study was conducted in Nasiriyah City, said the number of infected men more than women and children, and this goes back several reasons in men and through the study also found Variation in infection to the health center. Some centers recorded the highest cases of infection from tuberculosis during this year’s, some did not score in three years, an infection in Nasiriyah, the second sector is generally more than the infection in the first sector.It is during our visit to the health centers in the Nasiriyah to first and second Nasiriyah sector and updating us on the data found Also, the percentage fixed in Nasiriyah, from 2010 to 2015 among children, women and men, but the disparity in number by every year.Keywords: Tuberculosis, Nasiriyah city, Iraq.